2021
DOI: 10.1111/cmi.13325
|View full text |Cite
|
Sign up to set email alerts
|

Inositol polyphosphate–protein interactions: Implications for microbial pathogenicity

Abstract: Inositol polyphosphates (IPs) and inositol pyrophosphates (PP-IPs) regulate diverse cellular processes in eukaryotic cells. IPs and PP-IPs are highly negatively charged and exert their biological effects by interacting with specific protein targets. Studies performed predominantly in mammalian cells and model yeasts have shown that IPs and PP-IPs modulate target function through allosteric regulation, by promoting intra-and intermolecular stabilization and, in the case of PP-IPs, by donating a phosphate from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…With key structural and signalling roles, inositol is an important nutrient for fungal pathogens and C. neoformans can use inositol as a sole carbon source (48). Inositol polyphosphates (IPs) and inositol pyrophosphates (PP-IPs) are involved in regulation of diverse cellular processes such as chromatin remodeling, calcium and phosphate homeostasis, and cell cycle (37). In Schizosaccharomyces pombe , inositol pyrophosphate is involved in phosphate homeostasis (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With key structural and signalling roles, inositol is an important nutrient for fungal pathogens and C. neoformans can use inositol as a sole carbon source (48). Inositol polyphosphates (IPs) and inositol pyrophosphates (PP-IPs) are involved in regulation of diverse cellular processes such as chromatin remodeling, calcium and phosphate homeostasis, and cell cycle (37). In Schizosaccharomyces pombe , inositol pyrophosphate is involved in phosphate homeostasis (49).…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae (and other fungi), synthesis and vacuolar translocation of polyP is mediated by a polyP synthetase known as vacuolar transporter chaperone 4 or Vtc4 (5,36). Cells deficient in polyP synthetase have no detectable polyP and, for C. neoformans, this results in altered proliferation in the host and an impaired ability to trigger blood coagulation (37). Additionally, the genes XPP1 and EPP1 in C. neoformans encode putative exo- and endopolyphosphatases that catalyze the hydrolysis or mobilization of inorganic polyP in response to phosphate-limiting conditions (5).…”
Section: Introductionmentioning
confidence: 99%
“…Although not as famous as the sugars that are more commonly involved in energy metabolism, such as glucose and fructose, inositol plays critical regulatory roles in the cytoplasm and in membranes, where it is used to modify lipids. Cytoplasmic inositol can be phosphorylated on all six carbon positions; some of these sites can be dually phosphorylated (pyrophosphorylated), as part of signaling mechanisms that stimulate a wide range of cellular functions ( 1 ). Inositol also forms part of the structure of membrane lipids, such as glycophosphatidylinositol modification (GPI anchor) of the C-terminal tails of cell surface proteins to anchor them in the plasma membrane, and inositol modification of ceramides to create new sphingolipid varieties.…”
Section: Commentarymentioning
confidence: 99%
“…Recent studies in C. neoformans and C. albicans have shown that the inositol polyphosphate (IP) kinase (IPK) pathway is a promising target for antifungal drug development due to its involvement in numerous critical cellular processes (reviewed in [ 9 , 10 , 11 , 12 ]). The fungal IPK pathway is comprised of a series of sequentially acting IPKs that convert IP 3 to IP 8 , with IP 3-4 K the most critical for virulence and cellular function in both C. neoformans [ 13 , 14 , 15 , 16 ] and C. albicans [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to fungi, the product of IP 3-4 K, IP 5 , can be generated by more than one route in human and involves 4 different enzymes: inositol polyphosphate multikinase ( Hs IPMK), IP3K, INPP5 and ITPK1 (reviewed in [ 10 , 11 ]). In addition to having IP 3-4 K activity, Hs IPMK functions as a phosphoinositide 3-kinase [ 20 , 21 , 22 ] and as a scaffold protein in the target of rapamycin (TOR) where its enzymatic activity is not required [ 23 ] (reviewed in [ 24 ]).…”
Section: Introductionmentioning
confidence: 99%